2017
DOI: 10.1038/leu.2017.189
|View full text |Cite
|
Sign up to set email alerts
|

Irf8 regulates the progression of myeloproliferative neoplasm-like syndrome via Mertk signaling in zebrafish

Abstract: Interferon regulatory factor (IRF)-8 is a critical transcription factor involved in the pathogenesis of myeloid neoplasia. However, the underlying mechanisms in vivo are not well known. Investigation of irf8-mutant zebrafish in this study indicated that Irf8 is evolutionarily conserved as an essential neoplastic suppressor through tight control of the proliferation and longevity of myeloid cells. Surviving irf8 mutants quickly developed a myeloproliferative neoplasm (MPN)-like disease with enhanced output of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…S2) were then transfected into HEK293T cell line (ab255449, abcam), seperately. Protein was collected after 36 h transfection to perform Western blot according to the standard procedure 53 . Antibodies of mouse anti-HA (901501 Biolegend, 1:2000) and mouse anti-GAPDH (60004-1-lg Proteintech, 1:2000) were used for the detection.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2) were then transfected into HEK293T cell line (ab255449, abcam), seperately. Protein was collected after 36 h transfection to perform Western blot according to the standard procedure 53 . Antibodies of mouse anti-HA (901501 Biolegend, 1:2000) and mouse anti-GAPDH (60004-1-lg Proteintech, 1:2000) were used for the detection.…”
Section: Methodsmentioning
confidence: 99%
“…S2) were then transfected into HEK293T cell line (ab255449, abcam), seperately. Protein was collected after 36 h transfection to perform Western blot according to the standard procedure 53 .…”
Section: Western Blotmentioning
confidence: 99%
“…Targeted mutation of rps14 indeed led to anemic defects resembling those seen in 5q– syndrome (Ear et al, 2016), which was already modeled by morpholino oligonucleotide (MO) knockdown in a previous study (Payne et al, 2012). Besides, researchers also used transcription activator-like effector nucleases (TALENs) to generate mutations in the irf8 gene in zebrafish, which – as in mice – causes a type of MPN known as chronic myeloid leukemia (CML)-like disease (Holtschke et al, 1996; Zhao et al, 2018).…”
Section: Myeloid Neoplasmsmentioning
confidence: 99%
“…Remarkably, the authors showed that the abnormal phenotype in their model was associated with downregulation of the Notch pathway, which could be rescued by Notch overexpression in endothelial cells. Other models involve constitutive activation of stat5.1 (Lewis et al, 2006) or expression of known mutations involved in myeloid neoplasms (Barbieri et al, 2016; Bolli et al, 2010; Shi et al, 2015; Zhao et al, 2018). Although these models provide opportunities for further research, most of them do not fully recapitulate the features of human AML.…”
Section: Myeloid Neoplasmsmentioning
confidence: 99%
“…To study the role of interferon regulatory factor 8 (IRF8) in the pathogenesis of myeloid neoplasia, Zhao et al (2018) created a missense mutation, irf8 Δ57 that acted as a functional knockout. IRF8 is a critical transcription regulator for myeloid lineage commitment and closely tied to myeloid leukemia.…”
Section: Zebrafish Leukemia Models: Myeloid Originmentioning
confidence: 99%